Reconfiguring Logistics Strategies for Urban MSMEs - Wulandari, Safira (Omnia Tempus, 2025)
This research aims to explore the reconfiguration of logistics strategies for urban Micro, Small, and Medium Enterprises (MSMEs) in response to the unique challenges and opportunities posed by urban environments. The primary objective is to identify and analyze the logistical constraints faced by urban MSMEs, assess the role of technological innovations, and evaluate the integration of sustainability practices within logistics operations. The study adopts a qualitative research methodology, utilizing a comprehensive literature review of academic articles, books, and reports to synthesize findings on urban logistics management and supply chain strategies. By critically analyzing existing research, this study provides valuable insights into how urban MSMEs can adapt their logistics strategies to improve operational efficiency, enhance customer satisfaction, and contribute to environmental sustainability. The findings indicate that urban MSMEs face significant logistical challenges such as congestion, high operational costs, and fluctuating demand. Technological innovations, including cloud-based platforms, artificial intelligence, and machine learning, play a pivotal role in optimizing logistics processes, while sustainable practices such as green logistics and collaborative logistics strategies offer MSMEs opportunities to reduce costs and improve their environmental impact. The study concludes that urban MSMEs must embrace a more flexible and integrated approach to logistics management, combining technology, sustainability, and collaboration to stay competitive in an increasingly complex urban market. The research also highlights the need for further empirical studies to validate these findings and explore practical solutions for MSMEs in urban logistics.